The influence of peers and family problems towards drug abuse among youth: a case study at AADK Cure And Care Rehabilitation Center Kuala Muda / Ahmad Marzuki Zulkufly - Zulkufly, Ahmad Marzuki (2012)
The objective of the research is to discuss the issue of drug abuse among the youth. Realizing that the problem has become worse every day, the researcher is to find the whole true story about it. Through the research, the researcher has used several methods on gathered information from AADK Cure and Care Rehabilitation Center at Kuala Muda, Kedah. The research was held at the C&C Rehabilitation Center at Kuala Muda, where 57 trainers had been taken as the samples. The research shows that the main leading factor of drug abuse which is peers influence and family problems. The uncontrolled social life plants the seeds of curiosity in our hands together in order to beat and stop the disease from continuously destroying our younger generation.